2018
DOI: 10.1186/s12913-018-3656-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative point prevalence survey of antimicrobial consumption between a hospital in Northern Ireland and a hospital in Jordan

Abstract: BackgroundTo assess antimicrobial prescribing in a Northern Ireland hospital (Antrim Area Hospital (AAH)) and compare them with those of a hospital in Jordan (Specialty Hospital).MethodsUsing the Global-PPS approach, the present study surveyed patients admitted to the hospital in 2015, the prescribed antibiotics, and a set of quality control indicators related to antibiotics.ResultsUltimately, 444 and 112 inpatients in the AAH and the Specialty Hospital, respectively, were surveyed. For the medical group, 165 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Similar to previous studies [ 24 , 25 ], a high proportion of broad-spectrum antibiotic prescribing for surgical prophylaxis was noticed for several types of surgeries for more than one day in the included wards. Prolonged surgical prophylaxis was also common in Southern and Eastern Europe (85%, 86.3% respectively) [ 17 , 18 ], although it does not prevent the development of postoperative infections.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to previous studies [ 24 , 25 ], a high proportion of broad-spectrum antibiotic prescribing for surgical prophylaxis was noticed for several types of surgeries for more than one day in the included wards. Prolonged surgical prophylaxis was also common in Southern and Eastern Europe (85%, 86.3% respectively) [ 17 , 18 ], although it does not prevent the development of postoperative infections.…”
Section: Discussionsupporting
confidence: 86%
“…High adherence of prescriptions to the standard treatment guidelines in the current study (84.0%) is similar to previous studies in South Africa (98.0%), Northern Ireland (72.0%–81.8%), Jordan (92.2%–92.7%), Brazil (76.5%–87.3%) and Belgium (76.6%). 23–26 In contrast to these findings, a study in Nigeria found low adherence, ranging from 0.3% to 7.2%. 22 The finding of high adherence in Mbeya ZRH (94.0%), in contrast to the 63.0% found in 2018 by another study in the same hospital, may be accounted for by the possibility of postsurvey sensitisation and/or awareness.…”
Section: Discussionmentioning
confidence: 87%
“…To identify inappropriate antibiotic prescribing, we investigated five indicators of quality, which could easily be used to set benchmarks for quality improvement of antibiotic use in hospitals. [8] In our study, diagnosis was mentioned in 83.11% ( n = 64) of prescriptions [Figure 1]. Documentation of the reason for prescription ensures communication of diagnosis and treatment among clinicians and other health-care providers, and allows for recording of prescription stop or review dates and other interventions such as de-escalation.…”
Section: Discussionmentioning
confidence: 94%